Genetic algorithms for the single source capacitated location problem - Cortinhal, M.; M.E. Captivo (Metaheuristics, 2004)
The single source capacitated location problem is considered. Given a set of potential locations and the plant capacities, it must be decided where and how many plants must be open and which clients must be assigned to each open plant. Genetic algorithms that use different methodologies for handling constraints are described and tested. Computational experiments on different sets of problems are presented